1956
DOI: 10.3382/ps.0350054
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Energy Requirements of Chickens

Abstract: S TUDIES of the effects of différent dietary energy levels in the nutrition of laying hens hâve been limited. Heuser and coworkers (1945) were among the first to show that rations low in fiber content supported a higher rate of egg production than similar rations high in fiber content. Bird and Whitson (1946) studied layer rations of high and low fiber content with respect to productive efficiency and showed that efficiency was related inversely to fiber content. They were the first to use the Byerly (1941) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
2

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 4 publications
7
14
2
Order By: Relevance
“…The decrease in ADFI observed in hens fed the high energy diet was expected because poultry eat to satisfy their energy requirements, provided that the capacity of the GIT is not compromised (Hill et al, 1956;Leeson et al, 1997). Egg production and egg size were not affected by the energy content of the diet, consistent with data of Grobas et al (1999b) in brown hens Fig.…”
Section: Laying Phase Dietssupporting
confidence: 77%
“…The decrease in ADFI observed in hens fed the high energy diet was expected because poultry eat to satisfy their energy requirements, provided that the capacity of the GIT is not compromised (Hill et al, 1956;Leeson et al, 1997). Egg production and egg size were not affected by the energy content of the diet, consistent with data of Grobas et al (1999b) in brown hens Fig.…”
Section: Laying Phase Dietssupporting
confidence: 77%
“…The decrease in ADFI observed in hens fed the high energy diet was expected because poultry eat to satisfy their energy requirements, provided that the capacity of the GIT is not compromised (Hill et al, 1956;Leeson et al, 1997). Egg production and egg size were not affected by the energy content of the laying diet, consistent with data of Grobas et al (1999b) in brown hens fed diets varying in AME n from 2,680 to 2,810 kcal.…”
Section: Digestive Traits and Body Measurementssupporting
confidence: 76%
“…The decrease in ADFI observed in pullets and hens fed the high energy diet was expected because birds regulate voluntary FI to satisfy their energy requirements. Consequently, ADFI decreased and FCR improved as the energy concentration of the diet increased (Hill et al, 1956;Leeson et al, 1997).…”
Section: Effect Of Energy Concentration Of the Diet On Bird Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Feed intake is higher in low energy diet and lower in high energy diet. Hens fed with 1,848 kcal productive energy consumed 9.7% more feed than the hens provided with 2,046 kcal productive energy per kg of feed (Hill et al, 1956), increased in energy from 2,680 kcal to 2,810 kcal of ME/kg, and decreased the feed intake by 4% (Grobas et al, 1999). Similarly, Harms et al (2000) concluded that the hens fed with 2,519 kcal of ME/kg consumed 8.5% more feed than the hens fed with 2,798 kcal of ME/kg diet, and hens fed with 3,078 kcal of ME/kg diet consumed 3% less feed compared to the hens fed with 2,798 kcal of ME/kg diet.…”
Section: Introductionmentioning
confidence: 99%